Primary thyroid lymphomas - Mazur-Roszak, Małgorzata; Litwiniuk, Maria; Łącka, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2007)
Primary thyroid lymphoma (PTL) is a rare disease with heterogeneous histological and clinical characteristics. As a result, diagnosis and subsequent management of the disease is difficult. PTL occurs most commonly in the thyroid glands with a background of Hashimoto’s thyroiditis. The clinical presentation was usually an enlarging neck mass squeezing the surrounding structures. Most patients can be diagnosed by fine-needle aspiration (FNA) followed by immunophenotypic analysis, obviating the need for open surgical biopsy. Main histopathologic subtypes are either diffuse large B cell lymphomas (DLBCL) or mucosa-associated lymphoid tissue (MALT). Patients with localised, low-grade MALT lymphomas may be treated with surgery. Postoperative chemotherapy or radiotherapy is necessary in some patients. Systemic chemotherapy is the optimal treatment for DLBCL. In this group surgery may be used for palliative debulking to alleviate obstructive symptoms. Prognosis for MALT lymphoma is good. Diffuse large B cell lymphoma patients have poor prognosis (5-yr survival <50%). What should be stressed here is that patients with rapidly growing nodular goitre with or without cervical adenopathy should always be examined for primary thyroid lymphoma.